2022
DOI: 10.1007/s10615-022-00844-0
|View full text |Cite
|
Sign up to set email alerts
|

“There is Just a Different Energy”: Changes in the Therapeutic Relationship with the Telehealth Transition

Abstract: The therapeutic relationship (TR), including its therapeutic frame, is the foundation of the therapeutic endeavor. In response to the COVID-19 pandemic and the rapid transition to videoconferencing for therapeutic encounters, we employed a cross-sectional exploratory survey with 1490 respondents to understand how practitioners adapted to the changes. In this secondary analysis focused on the TR, we analyze the clinicians’ (N = 448) spontaneous narratives about facets of the TR. Temporally, we focused on how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…Finally, the common use of background blurring or opacification can remove an opportunity to appreciate environmental cues. In total, these truncations are likely responsible for the widespread perception of emotional deadening in telehealth settings 59 …”
Section: Missing or Truncated Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the common use of background blurring or opacification can remove an opportunity to appreciate environmental cues. In total, these truncations are likely responsible for the widespread perception of emotional deadening in telehealth settings 59 …”
Section: Missing or Truncated Channelsmentioning
confidence: 99%
“…In total, these truncations are likely responsible for the widespread perception of emotional deadening in telehealth settings. 59 Solutions to the visual channel issues may be forthcoming. Beyond the obvious fix of full field-of-view cameras (including digitally reconstructed video feeds), telehealth practitioners are actively experimenting with augmented reality and virtual reality.…”
Section: Missing or Truncated Channelsmentioning
confidence: 99%
“…Many healthcare activities were stopped because of social isolation measures (20, 23,25,28). Five studies (22)(23)(24)(25)29) reported telemedicine as one of the strategies for maintaining the home-based primary care service and its challenges, such as technical difficulties in approaching patients amidst the pandemic. Researchers also stated how community health workers adjusted the services to meet their needs, such as arranging case management outreach, coordinating elderly services and providing assistance to secure the basic needs of their home-based community care services (20, 21, 28, 30, 31).…”
Section: Figurementioning
confidence: 99%
“…Lethin et al ( 26 ) reported how community organization support affected the mental health of home care staff in four European countries. Many healthcare activities were stopped because of social isolation measures ( 20 , 23 , 25 , 28 ). Five studies ( 22 25 , 29 ) reported telemedicine as one of the strategies for maintaining the home-based primary care service and its challenges, such as technical difficulties in approaching patients amidst the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Research exploring remote mental health provision during Covid-19 has tended to use primarily survey methods and/ or to focus on the experiences of speci c practitioner groups such as family therapists or psychotherapists (e.g. [10][11][12][13][14][15][16] ). While many practitioners in these studies report positive experiences, attributing these to having greater exibility, being able to continue providing support, and patients feeling more able to share in sessions; concerns are also raised about di culties assessing patient safety, weaker therapeutic relationships, therapist fatigue, and possible digital exclusion 10-11,13−14 .…”
Section: Introductionmentioning
confidence: 99%